Adrenocortical carcinoma and pulmonary embolism from tumoral extension. (25th November 2019) - Shekhar, Skand; Gubbi, Sriram; Papadakis, Georgios Z; Nilubol, Naris; Hannah-Shmouni, Fady
Abstract : Summary: Adrenococortical carcinoma (ACC) is a rare cancer, occurring at the rate of one case in two million person years. Cushing syndrome or a mixed picture of excess androgen and glucocorticoid production are the most common presentations of ACC. Other uncommon presentations include abdominal pain and adrenal incidentalomas. In the present report, a 71-year-old male presented with abdominal pain and was eventually diagnosed with ACC. He was found to have pulmonary thromboembolism following an investigation for hypoxemia, with the tumor thrombus extending upto the right atrium. This interesting case represents the unique presentation of a rare tumor, which if detected late or left untreated is associated with poor outcomes, highlighting the need for a low index of suspicion for ACC when similar presentations are encountered in clinical practice. Learning points: ACC is a rare but aggressive tumor. ACC commonly presents with rapid onset of hypercortisolism, combined hyperandrogenism and hypercortisolism, or uncommonly with compressive symptoms. Clinicians should have a low index of suspicion for ACC in patients presenting with rapid onset of symptoms related to hypercortisolism and/or hyperandrogenism. Venous thromboembolism and extension of the tumor thrombus to the right side of the heart is a very rare but serious complication of ACC that clinicans should be wary of. The increased risk of venous thromboembolism in ACC could be explained by direct tumor invasion, tumor thrombi or hypercoagulability secondary to hypercortisolism. Early diagnosis and prompt treatment can improve the long-term survival of patients with ACC.